Pengaruh Brand Image Dan Promosi Media Digital Terhadap Minat Sewa Di Malang Creative Center - Laila Nur Azzizzah; Sanita Dhakirah; Rizky Kurniawan Murtiyanto (CV. ITTC INDONESIA, 2025)
Advances in information technology have brought significant changes in the way people communicate, conduct business and access information. Therefore, having a good brand image is a must for companies and institutions in order to gain trust from the public. This study aims to analyze the effect of brand image and promotion through digital media on rental interest in Malang Creative Center. This study uses a quantitative approach with brand image and digital media promotion as independent variables, while rental interest acts as the dependent variable. Data were collected by distributing questionnaires to 30 objects who are regular users of Malang Creative Center, with saturated sample selection technique. Data were analyzed using multiple linear regression and hypothesis testing. The findings of this study indicate that brand image and promotion through digital platforms have a positive and significant impact on rental interest in Malang Creative Center. Simultaneous tests also confirmed that both independent variables simultaneously influence rental interest. Based on these findings, it can be concluded that both separately and simultaneously, brand image and promotion through digital media have a positive and significant influence on rental interest in Malang Creative Center. Therefore, it is expected that Malang Creative Center continues to maintain and improve the quality of its brand image and digital promotion strategy to be more optimal.